Avelumab in unresectable/metastatic, progressive, grade 2–3 neuroendocrine neoplasms (NENs): Combined results from NET-001 and NET-002 trials. (July 2022) - Chan, D.L.; Rodriguez-Freixinos, V.; Doherty, M.; Wasson, K.; Iscoe, N.; Raskin, W.; Hallet, J.; Myrehaug, S.; Law, C.; Thawer, A.; Nguyen, K.; Singh, S.
Abstract: Background: Higher grade neuroendocrine neoplasm (NENs) continues to pose a treatment dilemma, with the optimal treatment undefined. Although immunotherapy has revolutionised the treatment of many cancers, its role in NENs remains unclear. We aimed to investigate the efficacy and safety of avelumab, a PD-L1-directed antibody, in patients with advanced unresectable/metastatic higher grade NENs. Methods: NET001 and NET002 are phase II studies investigating avelumab (NCT03278405 and NCT03278379). Eligible patients had unresectable and/or metastatic WHO G2-3 NENs from a gastroenteropancreatic (GEP) source or a bronchial primary (excluding typical carcinoid) and 0–2 prior lines of systemic therapy (excluding SSAs). Patients were treated with avelumab 10 mg/kg intravenously every two weeks for 26 cycles. NET001 investigated G3 poorly differentiated GEP neuroendocrine carcinomas (NECs) and bronchial small/large cell NEC, whereas NET002 investigated G2-3 well-differentiated GEPNETs and bronchial atypical carcinoids. The primary endpoint in both trials was overall response rate (ORR) by RECIST v1.1; secondary endpoints included progression-free survival, overall survival, disease control rate at six months and toxicity. Results: Twenty-seven patients were enrolled (21 GEP, 6 lung; 10 in NET-001, 17 in NET-002); median age 64 (range 37–80), 30% ECOG PS 1–2 and 78% received 1+ lines of prior therapy. The median Ki-67 index was 35% (range 10–100). Twelve of the twenty-seven patients had died at the time of data lock. The median time on treatment was 85 days (seven cycles). No objective responses were observed. Stable disease was achieved in 33% of patients, and the disease control rate at 6 mo was 21%. The median PFS was 3.3 months (range 1.2–24.6), and the median OS was 14.2 months. Treatment-related adverse events (all grades) occurred in 58% of patients. Three patients had treatment-related grade 3–4 AEs leading to treatment discontinuation (immune-related hepatitis n = 2 and infusion-related reaction n = 1). Conclusion: Single-agent PD-L1 blockade with avelumab showed limited antitumour activity in patients with G2-3 NENs. Correlative studies are underway. Further studies are needed to explore the role of dual immunotherapy and other combinations in this population with few treatment alternatives. Highlights: There are few treatments for high-grade advanced neuroendocrine neoplasms (NENs). We treated 27 patients with advanced NENs with avelumab, a PD-L1-directed antibody. No objective responses were observed; stable disease was achieved in 33% of patients.